Experimental and Numerical Investigations of Dynamic Failure Mechanisms of Underground Roadway Induced by Incident Stress Wave - Zhi-Long He; Cai-Ping Lu; Xiu-Feng Zhang (Applied Sciences, 2022)
The mechanisms of dynamic disasters around underground roadways/tunnels were examined by adopting split Hopkinson pressure bar (SHPB) laboratory tests to reproduce the failure process of the surrounding rock subjected to incident stress waves. On the basis of ensuring the consistency of numerical simulations with the experimental results, the failure mechanisms of the surrounding rock and spatiotemporal evolution of the hoop stress around the hole were studied by using a two-dimensional particle flow code (PFC2D). The results of the numerical simulation indicate that tensile stress and compressive stress concentrate along the horizontal and vertical directions around the hole, respectively, owing to the instantaneous incidence of compressive stress waves. The failure modes of surrounding rocks are significantly different when the hole is subjected to various intensities of incident stress waves. In addition, the stability of the surrounding rock of the hole is greatly affected by the amplitude and wavelength of the incident wave and the elastic modulus of the surrounding rock.